Mesoporous silica nanoparticles loaded Au nanodots: a self-amplifying immunotherapeutic depot for photothermal immunotherapy - Wang, Chuan; Wang, Dongmei; Huang, Liang; An, Qi (Frontiers in Immunology, 2025)
IntroductionPhotothermal therapy (PTT) has emerged as a highly promising approach for cancer treatment due to its advantages of localized treatment, controllable irradiation, and non-invasive nature. This study presents a multifunctional platform for tumor PTT based on Au nanoparticles-decorated mesoporous silica nanoparticles (MSN@Au), aiming to synergize photothermal ablation with immune modulation.MethodsMSN@Au nanoparticles were engineered as the PTT agent. Photothermal efficiency was evaluated under 808 nm near-infrared (NIR) laser irradiation. Anti-tumor efficacy was systematically assessed both in vitro (tumor cell cultures) and in vivo (tumor-bearing animal models). Immune responses were analyzed by examining immunogenic cell death (ICD) induction, dendritic cell maturation, and cytotoxic T cell activation/infiltration within the tumor microenvironment (TME).ResultsMSN@Au demonstrated exceptional photothermal conversion efficiency under NIR irradiation, leading to significant tumor cell inhibition in both in vitro and in vivo. Mild PTT mediated by MSN@Au not only caused direct tumor cell damage but also triggered ICD. This promoted dendritic cell maturation and enhanced activation/infiltration of cytotoxic T cells within the TME, thereby amplifying anti-tumor immunity.DiscussionThis study underscores that the strategic design of MSN@Au as a PTT agent successfully induces ICD while modulating the immunosuppressive TME, significantly amplifying therapeutic efficacy. The integration of efficient photothermal ablation with immune activation opens new avenues for developing next-generation nanoplatforms that synergize PTT with immune modulation, offering a promising strategy for treating solid tumors.